Effectiveness of GenRe kit health promotion media on reproductive health knowledge among adolescents - Ahsanu Bil Husna; Muh Arfah; Zilvi Fuadiyah Nur; Tausyiah Rohmah Noviyanti (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2026)
Introduction: Ensuring healthy lives and promoting well-being, including maintaining reproductive health, is one of the key targets of the SDGs, which is especially crucial during adolescence when sexual maturity begins, and inadequate knowledge can increase the risk of reproductive-health problems. The use of appropriate and engaging methods and media will be more effective in increasing knowledge. Learning through play using the GenRe Kit can be an alternative to enhance students’ knowledge, particularly about reproductive health. This study aimed to determine the effect of using the GenRe Kit (Snakes and Ladders and Reproductive Organ Apron) as a health promotion medium on the level of adolescents’ knowledge of reproductive health at SMP Dharma Kirti, Karangasem Regency, Bali.Methods: This research was a quantitative study that used a quasi-experimental design with a one-group pretest and posttest approach. It was conducted at SMP Dharma Kirti, Karangasem Regency, Bali, in August 2024, with 30 ninth-grade students as participants.Results: The results of this study showed that before the intervention using the GenRe Kit, the participants (n = 30) were given a pretest, with a minimum score of 45 and a maximum score of 95. The average pretest score was 74.33 with a standard deviation of 13.8. After the intervention, the participants were given a posttest, and the results indicated that the average posttest score was 82.17 with a standard deviation of 10.05. The minimum score obtained in the posttest was 60, while the maximum score was 95.Conclusions: The GenRe Kit intervention produced a significant improvement in adolescents’ reproductive-health knowledge (Δ = 7.84, p = 0.001) and demonstrates its practical value as an interactive learning tool that can support school-based reproductive-health education and strengthen efforts to achieve relevant SDG targets.